EMPIRICAL ANALYSIS OF THE ECOLOGICAL AND SOCIAL ENVIRONMENT OF THE QUALITY OF LIFE OF THE POPULATION OF THE CARPATHIAN REGION OF UKRAINE - VASYLTSIV, TARAS; MULSKA, OLGA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article presents the results of the development of the author’s methodological approach to assessing the determinants of the ecological and social environment of the quality of life of the population of the region. The aim of the article is to develop a methodological approach and analyze the social and environmental components of the quality of life of the population of the region. A system of indicators for assessing the environment of the quality of life of the population has been formed. Within the social component, the indicators are represented by groups: employment, income, living conditions; social welfare; social tension; provision of social infrastructure. Within the environmental component, the indicators are represented by groups: the availability of water resources; pollution of territories, air quality; investment provision of nature management; provision of land. The coefficients of weight of indicators are determined (using temporal weight coefficients and the theory of elasticity). Integral coefficients of social and ecological environment of quality of life in Ukraine and its Carpathian region are constructed. The method of studying the ecological and social environment of the quality of life of the population involves the implementation of 5 stages: the formation of homogeneous time series; construction of temporal weights using the theory of elasticity, which allows to take into account the sensitivity of the integrated indicator of the quality of life environment to changes in social and environmental indicators; calculation of weighted coefficients of indicators within the group of indicators; construction of weighted coefficients of subsystems and construction of integrated coefficient of quality of life environment. The practical significance of the results of the study lies in the possibility of applying the methodology for assessing the integrated level of social and environmental environments in the context of their impact on quality of life, and, consequently, drawing conclusions about the effectiveness of regional policy in this area; identification of the factors that have the greatest impact on the quality of life, as well as factors that need improvement. The scientific novelty of the research results is the development of a new methodological approach to the analysis of quality of life factors with the use of an innovative approach to the calculation of weights of indicators.